Identifying the factors affecting individual resistance against organizational change - Küçükatalay, Tuğba; Vardarlıer, Pelin; Özsürünç, Recep; Vayvay, Özalp (Ali Khorsandi Taskoh, 2023)
This study aims to determine the factors affecting individual resistance. Literature review shows that job insecurity, emotional distress, and identity division are potential variables that will affect individual resistance. As a result of the factor and reliability analysis, the emotional distress scale consisted of 3 sub-factors: excitement, anxiety, and enthusiasm. Individual resistance, job insecurity, and identity fragmentation scales emerged as the only factors. As a result of simple and multiple regression analyses, it is seen that all independent variables significantly affect individual resistance. Job Insecurity has a significant and positive effect on individual resistance. It is seen that anxiety has a significant and negative effect on individual resistance, and enthusiasm has a significant and positive effect. The identity division has a significant and positive effect on individual resistance. Anxiety and enthusiasm variables, which are the sub-dimensions of emotional distress, are the variables that most affect individual resistance. In order to encounter less resistance and problems in the change process, employees need to be trained and prepared for a change in advance. Organizational change can only be achieved with the participation and support of employees. The study concludes with recommendations for managers at the strategy, operations, and human resources management levels.
Keywords: Emotional Distress; Identity Division; Individual Resistance; Job Insecurity; Organizational Change